2003
DOI: 10.1002/jcu.10171
|View full text |Cite
|
Sign up to set email alerts
|

Doppler measurement of blood flow velocities in extraocular orbital vessels in patients with obstructive sleep apnea syndrome

Abstract: Color Doppler sonographic measurements of blood flow parameters in the orbital vessels may differ significantly between patients with OSAS and those without the syndrome. Therefore, OSAS should be considered in addition to other conditions when interpreting the results of color Doppler sonography of the extraocular orbital vessels if the clinical history points toward such a diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…These data are consistent with a previous study indicating that blood flow parameters in the orbital vessels were significantly different between patients with sleep apnea and those without the condition [75]. Specifically, among patients with mild sleep apnea, peak systolic velocity and end diastolic velocity in the posterior ciliary arteries were significantly higher than those observed for the control group [75]. In the next two sections, we discuss the effects of hypertension and obesity on the relationships between glaucoma and sleep apnea and the hypothesized effects of sleep apnea on ocular blood flow.…”
Section: Complex Relationships Between Sleep Apnea and Glaucomasupporting
confidence: 93%
See 1 more Smart Citation
“…These data are consistent with a previous study indicating that blood flow parameters in the orbital vessels were significantly different between patients with sleep apnea and those without the condition [75]. Specifically, among patients with mild sleep apnea, peak systolic velocity and end diastolic velocity in the posterior ciliary arteries were significantly higher than those observed for the control group [75]. In the next two sections, we discuss the effects of hypertension and obesity on the relationships between glaucoma and sleep apnea and the hypothesized effects of sleep apnea on ocular blood flow.…”
Section: Complex Relationships Between Sleep Apnea and Glaucomasupporting
confidence: 93%
“…Preliminary data obtained from 31 patients with sleep apnea undergoing orbital doppler ultrasonography suggests a positive correlation between the ophthalmic artery resistivity index and the mean visual field defect, pointing to the possibility that visual field defects might be due to optic nerve perfusion defects [74]; of note 12.9% of the patients with glaucoma in that study had sleep apnea. These data are consistent with a previous study indicating that blood flow parameters in the orbital vessels were significantly different between patients with sleep apnea and those without the condition [75]. Specifically, among patients with mild sleep apnea, peak systolic velocity and end diastolic velocity in the posterior ciliary arteries were significantly higher than those observed for the control group [75].…”
Section: Complex Relationships Between Sleep Apnea and Glaucomasupporting
confidence: 92%
“…In addition, in a study where ophthalmic artery resistance and central artery resistance were examined in patients with OSAS by Doppler ultrasonography, it was found that there is no significant difference in vascular resistance and intraocular pressure however, there was a positive correlation between AHI and IOP; nonetheless, no difference was between IOP of the two groups [24]. Erdem et al reported that they measured postsystolic and enddiastolic volumes by Doppler ultrasonography in patients with severe OSAS; the blood flow was significantly increased in ophthalmic artery, in central retinal artery, and in posterior ciliary artery, whereas in patients of mild OSAS the blood flow increased only in posterior ciliary artery [25]. This increase may be a compensatory response occurring against chronic hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia indirectly increased intracranial pressure during sleep and decreased cerebral perfusion pressure may disturb blood supply of the optic nerve in patients with OSAS. 2,6,27,28 Orbital blood flow measured by colour Doppler ultrasonography was found to be higher in patients with OSAS compared to controls and increase in blood flow was accepted as a vasodilatory response to hypercapnia, one of the most important 29 Vascular disturbances may result with diffuse loss or localized defects of the RNFL before initation of glaucoma. 30 When vascular dysregulation in OSAS is added to nocturnal systemic hypotension, RNFL damage and consequent thinning may occur.…”
Section: 12-14mentioning
confidence: 99%